KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MEWUJUDKAN SMK YANG BERDAYA SAING - Virnindo, Algusri; M, Giatman; Yuliarma, Yuliarma; Mardizal, Jonni (STKIP Pesisir Selatan, 2025)
This study aims to gain an in-depth understanding of the implementation of transformational leadership by the principal in developing a competitive and innovative school at SMK Negeri 5 Solok Selatan. The study uses a case study method by conducting literature studies and interviews with leaders, teachers, administrative staff, students, and the school committee. An in-depth analysis was conducted on the implementation of transformational leadership applied by the principal, the strategies used, and the identification of supporting and inhibiting factors, as well as the impact of the application of transformational leadership. The implementation of transformational leadership was viewed from four main dimensions, namely Idealized Influence, Intellectual Stimulation, Inspirational Motivation, and Considerate Behavior. The results of the study show that the transformational leadership applied by the principal at SMKN 5 Solok Selatan was able to increase the school's competitiveness as assessed by three indicators, namely school achievement, teacher qualifications, and student achievement in academic and non-academic fields. This study fills a gap in the literature by presenting holistic empirical evidence (through in-depth case studies) that transformational leadership is the main causal factor capable of mobilizing internal resources (teachers and students) to achieve all three competitiveness indicators simultaneously, particularly in the vocational school environment in South Solok.